Boswellic Acid Loaded Nanoemulgel for Rheumatoid Arthritis: Formulation Design and Optimization by QbD, in vitro, ex vivo, and in vivo Evaluation - Amgaonkar, Yogesh Mahadeo; Kochar, Nitin Indarchand; Chandewar, Anil Vishwanath; Umekar, Milind Janrao; Wadher, Kamlesh Jayantilal (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Topical delivery of medication is often considered to be the best choice due to benefits such as avoidance of gastric degradation, first pass metabolism along with effortless application and retrieval. In topical delivery, the types of the vehicles and the physicochemical characteristics of drug are the prime variables that control the drug release and the therapeutic efficacy. The main component of Boswellia, Boswellic Acid (BA), is assumed to be accountable for the majority of pharmacologic effects. Nanoemulgel combines the benefits of nano-emulsions and the gels. Materials and Methods: The present work carried out with an objective of formulation of topical nanoemulgel of boswellic acid containing carbopol 934 and liquid paraffin as oil base. Results: The prepared nanoemulgel characterized for the various parameters such as, in vitro, ex vivo permeation and in vivo anti-inflammatory activity. The optimized nanoemulsion consisted of carbopol 934 and surfactant mix ratio (tween 80:Span20::1:1), in 1, 1.5 and 2 % w/w. The in vitro, ex vivo permeation of BA from nanoemulgel were found to be 90±0.33% and 85.5±1.2% at 12 hr respectively. Conclusion: Topical application of BA nanoemulgel formulation significantly reduced the inflammation by reducing the serum IL-6 concentration compared with the arthritic rats. The research findings showed that BA nanoemulgel has the ability to increase penetration through the skin and produce an anti-inflammatory impact.
Keywords: Boswellic acid; Nanoemulgel; Anti-inflammatory effect; Rheumatoid arthritis; Topical; delivery